MAKING A SYNTHETIC ZEOLITE FROM A RESIDUE OF BAUXITE WASHING - Kukuh Nur Hidayat; Agus Wahyudi; Husaini Husaini (Indonesian Mining Journal, 2020)
A zeolite synthetic of NaA type is generally prepared by mixing the alumina and silicate-containing materials (alkali alumino hydro-silicates). The used raw materials include the amorphous solids such as metakaolin, siliceous earth, coal ash, kimberlite waste, alumina trihydrate [Al(OH)3], bauxite, and aluminum metal. Residue of bauxite washing retains a fine texture and contains significant alumina and silica content, namely 30-36% Al2O3 and 10-15% SiO2. Both components are required for making the zeolite NaA . In this research, the zeolite NaA was made by extracting the alumina from residue of bauxite washing with caustic soda, and followed by reacting it with a water glass after through the flushing and washing process. The composition of zeolite NaA is as follows: 33.87% SiO2, 27.63% Al2O3, 16.31% Na2O, and 22.18% H2O with Na96Al96Si96O384.216H2O or Na12(AlO2)12(SiO2)12.27H2O as its mineral composition.